Critical and Analytical Look at the Form and Content of The Book Resistance Literature - Morteza Zare Beromi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book “Resistance Literature” (1970) by Ghali Shokri is a critique of resistance in literary genres. The main subject of this book is about heroes in literary types. The literary works contained in this book are a collection of novels, myths, theaters and poems for the nations. The analysis of Resistance Literature is based on a descriptive and analytical approach. We also rely on critical and analytical methods in writing this paper. Structural evaluation for this book includes the following: Cover design, book title, index, language, page layout, references, footnotes, and index for information. And content evaluation is done according to the author’s analysis about hero and heroism in literary types. The research results indicate: Cover design, book title and index need to be reviewed, the language of the book is written smoothly, the book’s content is unbalanced between literature against nations, 64.66% of the book’s ability is devoted to Arabic literature and 35.34% to literature in other countries, the author is interested resistance literature in Egypt and France, more than other countries.